Digital Marketing Capability and Performance: Moderated Mediation Approach - Sathana, V. (University of Kelaniya, 2025)
The study aims to identify the nexus between digital marketing capability and the performance of small and medium enterprises, as well as the moderated mediation effect of competitive intensity and relationship marketing. Quantitative methodology is appropriate for analysing the above nexus. I adopted convenient sampling to select the respondents and developed a structured questionnaire to collect data from the respondents. Structural equation modelling analysis was applied to analyse the influence, mediation effect, and moderation effect; the SPSS process was applied for moderated mediation analysis. The result revealed that digital marketing significantly influences performance and relationship marketing. Relationship marketing significantly influences the performance of SMEs. Relationship marketing significantly mediates the relationship between digital marketing capability and the performance of SMEs. Competitive intensity significantly moderates the relationship between relationship marketing and the performance of SMEs. The indirect effect of digital marketing on the performance of SMEs via relationship marketing significantly reduces as the competitive intensity level increases from low to high. This study offers significant academic contributions. It introduces a comprehensive moderated mediation mechanism to explore how digital marketing capability impacts SME performance, with relationship marketing acting as a mediator and competitive intensity as a moderator. The findings confirm the mediation effects and provide robust evidence for the moderated mediation mechanism, filling a gap in SME marketing literature by emphasising digital marketing’s role in improving performance. Additionally, the study may face challenges in capturing the dynamic nature of competitive intensity, which can vary with market conditions and technological advancements.
Keywords: Competitive Intensity; Digital Marketing Capability; Performance; Relationship Marketing; Small and Medium Enterprises